PEREMPUAN DAN KEWARGANEGARAAN DI INDONESIA: KASUS BALI, SASAK, DAN MINAHASA - Amin Mudzakkir (Jurnal Masyarakat dan Budaya, 2013)
Citizenship is a gendered practice. Although normatively it try to transcend differences of identities, such as gender, into national identity, in reality it is challenged by particular identities. In Indonesia, those particular identities are ethnicity and religion that growing in tandem with the dynamics ofIndonesian nationhood models. The focus of this paper is the dynamics of women citizenship in the post-Soeharto Bali,Lombok, and Minahasa. As conclusion, women citizenship is a reflection of a complex relationship between the individual,ethnic/religious community and the state. In this triangular relationship, the role of the state is crucial. Keywords: women, citizenship, Indonesia, Bali, Lombok, Minahasa.